2013
DOI: 10.4103/0971-5851.113404
|View full text |Cite
|
Sign up to set email alerts
|

Palliative chemotherapy in head and neck squamous cell cancer - What is best in Indian population? A time without symptoms, treatment toxicity score based study

Abstract: Background:Patients with recurrent and metastatic head and neck Squamous Cell Cancer (HNSCC) have poor prognosis with limited treatment options. In view of decimal prognosis, the treatment decision should include quality of life (QOL) issues, cost-effectiveness besides the response rates and survival.Aim:Present retrospective analysis was conducted to evaluate efficacy (disease-free survival), pharmacoeconomics, and toxicity profile of four (4) different regimens, viz. gefitinib alone, gefitinib with methotrex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…It decreases the patient's quality of life (QOL) following HNC treatment (Kalyanam et al, 2018;Anuradha et al, 2013). QOL is considered to be an important factor in both treatment decision and outcome evaluation (Anuradha et al, 2013;Blazeby et al, 1995;Maciejewski et al, 2010;Gonçalves et al, 2012). Particularly, QOL is necessary in multidirectional analysis and appropriate evaluation of treatment results.…”
Section: Introductionmentioning
confidence: 99%
“…It decreases the patient's quality of life (QOL) following HNC treatment (Kalyanam et al, 2018;Anuradha et al, 2013). QOL is considered to be an important factor in both treatment decision and outcome evaluation (Anuradha et al, 2013;Blazeby et al, 1995;Maciejewski et al, 2010;Gonçalves et al, 2012). Particularly, QOL is necessary in multidirectional analysis and appropriate evaluation of treatment results.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient population was similar to other reports, i.e., predominantly male population and in the fourth/fifth decade of life. [ 5 7 9 ] We had nearly an equal proportion of de novo patients as well as radical treatment failed patients. Expectedly, pain was the predominant feature in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…in 68 patients concluded that 75% patients had a meaningful clinical response which has further effect on symptom improvement with weekly methotrexate ± geftinib. [ 9 ] Other study by Banipal and Mahajan showed a very good clinical response with decrease in the tumor bulk by more than 50% in nearly 40% patients and further 40% has stable disease with weekly injection methotrexate. [ 14 ] A study by Patil et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumptions of tobacco (smoking and chewing), alcohol and HPV infection are well-known risk factors toward the development and progression of head and neck squamous cell carcinoma (HNSCC) [ 2 , 3 ]. In India, HNSCC has profound smoking, betel quid and tobacco chewing profile and comparatively poor survival [ 4 6 ]. However, HPV positive (+) HNSCC had distinct risk profile and associated with a better survival compared to HPV negative (-) HNSCC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%